From prosperity to decline : eighteenth century Bengal - Chaudhury, Sushil (New Delhi : Manohar, 1995)
Impact of trade on the economy of Bengal in 18th century.
Includes bibliographical references (p. [356]-367) and index.
Keywords: Bengal (India) -- Commerce